Neurorretinitis asociada a infección por Bartonella henselae: reporte de un caso clínico y revisión de la literatura - Arce G., Natalia; González V., Esteban; Madrid S., Valeska (Revista Hospital Clínico Universidad de Chile, 2017)
Cat scratch disease (CSD) is an infectious disease produced by Bartonella henselae. It typically causes fever, regional adenopathy, an inoculation zone papule and malaise. It is transmitted by a cat scratch or bite. Infrequently has atypical manifestations like neuroretinitis, which usually manifests as unilateral and painless decrease of visual acuity. We present a clinical case and review of the literature. A seven-year-old girl with malaise, fever and weight loss who iniciated blurred vision in superior hemifield of the left eye. Alterations concordant with neuroretinitis were seen in the fundus of the eye without other findings at physical examination. An infection by Bartonella henselae was objectified, making the diagnosis of CSD associated neuroretinitis. The pacient received antibiotic treatment achieving total clinical improvement. The diagnosis of CSD associated neuroretinitis is based on clinical criteria, useful to guide the etiologic study, and laboratory exams that allow to confirm it, being indirect inmunofluorescence and ELISA the most usedtest, for their high efficiency. Once the diagnosis is confirmed, the treatment is performed with bi-associated antibiotic therapy, being adjusted according to the patient’s age. Irreversible sequelae can be caused by CSD associated neuroretinitis, so it is recommended to treat it and maintain subsequent periodic controls.